Priorities and Threats of Antibiotic Resistance - Tarro, Giulio (British Journal of Healthcare and Medical Research, 2023)
The history of the antibiotics would now be too long to be reported in detail. However, since the middle of the last century, after a first attempt made by sulfonamides, before, during and after the Second World War, it was precisely their discoverers who laid the foundations for the modalities of a therapeutic treatment which undoubtedly radically changed the life expectancy of most of the known infectious diseases, especially as regards the world of bacteria. Therefore, we report their formulas together with the great scholars who discovered them.